Responses of Arbuscular Mycorrhizal Fungi Diversity and Community to 41-Year Rotation Fertilization in Brown Soil Region of Northeast China - Zhang, Shiyu; Luo, Peiyu; Yang, Jinfeng; Irfan, Muhammad; Dai, Jian; An, Ning; Li, Na; Han, Xiaori (Frontiers in Microbiology, 2021)
Arbuscular mycorrhizal fungi (AMF) play vital roles in the growth and development of plants, ecosystem sustainability and stability in agro-ecosystem, such as transporting nutrients to host plants, improving soil physical structure, and enhancing the stress resistance of host plants. However, the effects of fertilization on AMF diversity and community in brown soil areas are still unclear. The purpose of this study is to explore changes in AMF diversity and community structures and finding out the factors that influenced the changes after 41-year of fertilization in brown soil. Samples were collected from five treatments of the long-term fertilization experiment in June 2019, including CK (no fertilizer), N (mineral nitrogen fertilizer), NP (mineral nitrogen and phosphate fertilizer), M (pig manure), and MNP (pig manure, mineral nitrogen, and phosphate fertilizer). Illumina HiSeq sequencing was used to determine AMF diversity and community structure. The relationship between AMF communities in soil and roots and environmental factors were analyzed by redundancy analysis. The results showed that the soil nutrient content of manure treatments was generally higher than that of chemical fertilizer treatments and no fertilizer treatment. Long-term fertilization increased AMF spore density which increased with the increase of soil fertility. The moderate content of soil available phosphorus was beneficial to the colonization of AMF. AMF diversity in soil decreased with soil fertility, but AMF diversity in roots only influenced by soil nitrate-nitrogen and pH. Glomus was the dominant genus in both soil and root samples. AMF community structure in soil and roots had a different response to long-term fertilization. Application of manure had a greater impact on AMF community structure in soil, while application of exogenous phosphate fertilizer had a greater impact on that in roots. Soil ammonium nitrogen, nitrate-nitrogen, total nitrogen, organic carbon, total potassium, and available potassium were the most important factors that influenced taxa of AMF in soil, while soil ammonium nitrogen, nitrate-nitrogen, total nitrogen, organic carbon, total potassium, available potassium, available phosphorus, and plant phosphorus and potassium content were the most important factors influencing taxa of AMF in maize roots under long-term fertilization in brown soil.